Forecasting Tingkat Kesehatan dan Ketahanan Perbankan di Indonesia - Hamdillah, Dwinisa; Ermawati, Wita Juwita; Suprayitno, Gendut (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2024)
The number of commercial banks in Indonesia after the 2008 global crisis declined. The decrease in this number was caused by mergers, consolidations, acquisitions, integrations and conversions in the context of forming a resilient national banking industry structure. To ensure a stable banking sector, these banks must be evaluated through a Risk-based Bank Rating. When the 2008 global crisis economic shock and the COVID-19 pandemic occurred, the banking intermediary function was disrupted. In these conditions, the financial performance of banks also experienced a decline. This study aimed to assess the bank rating and resilience of banks in 2008-2020, forecast the bank rating and resilience of banks in Indonesia in 2021-2030 and analyze the effect of bank rating on bank resilience. This study used secondary data, that is a annual financial reports published by the Financial Services Authority. The data was analysed by ARIMA and panel data regression. The results showed that the bank rating and resilience of commercial banks declined during the economic shocks of the 2008 global crisis and the 2020 Covid pandemic. It is predicted that the resilience of commercial banks will increase in 2021-2030. Earnings as measured by ROA had a positive effect on bank resilience. Credit risk (NPL) had a negative effect on resilience, while liquidity risk (LDR) showed a positive effect on the resilience of commercial banks in Indonesia. GCG and Capital had no effect on bank resilience